On the matter of the artificial intelligence impact on legal profession at digital era - Sinkevich, Kristina V. (Journal of the Belarusian State University. Law, 2021)
The article deals with the matters of practical application of artificial intelligence technology in legal activity. Having in mind that the effect of artificial intelligence technology on the field of law is getting higher from year to year, the author analyses the risks connected with possibility that the position of lawyers on the law service market will become weakened. Moreover, the article emphasises that implementation of artificial intelligence into the field of law places new demands on professional competencies of a lawyer in the context of digitalisation.